Strong inhibitory effects of Desmodesmus sp. on Microcystis blooms: Potential as a biological control agent in aquaculture - Bo Yang; Yuhua Li; Zihan Wang; Zhiguang Yue; Junqi Wen; Xueqin Zhao; Hu Zhang; Xianfeng Wang; Xiufen Wang; Man Zhang (Aquaculture Reports)
Microcystis blooms in aquaculture present a significant threat to economic interests and human health. The method of ‘algae suppression’ has shown potential in mitigating these blooms, with the inhibitory capabilities of the introduced algal species playing a crucial role. Recent studies have highlighted the potential of algae belonging to the Scenedesmaceae family in inhibiting Microcystis blooms. In this study, 13 algal strains from this family were screened, revealing that two strains of Desmodesmus sp. (COFHNU-0002 and COFHNU-0005) isolated from aquaculture ponds exhibited the most robust inhibitory effects on Microcystis. The inhibitory effects of these two strains were evaluated at temperatures of 25°C and 30°C, demonstrating increased inhibition at higher temperatures. Moreover, their inhibitory effects were assessed in fishpond water experiencing a Microcystis bloom, with the highest inhibition rate achieved when the inoculated ratio of the Desmodesmus sp. (COFHNU-0005) to Microcystis was 1:1, reaching up to 67.0 %. Investigation into the inhibition mechanisms of Desmodesmus sp. on Microcystis revealed, for the first time, that the active substances responsible for inhibition originate from its extracellular vesicles. Furthermore, Desmodesmus sp. possessed a high content of proteins and polyunsaturated fatty acids, consequently providing additional value for fish in aquaculture. As a result, Desmodesmus sp. shows potential as a biological control agent for controlling harmful Microcystis blooms, providing innovative technological support for the advancement of aquaculture.